Place Consciousness and School Leaders' Intentionality as Partnership Imperatives : Supporting the Recruitment of Quality Graduates in Regional, Rural and Remote Schools - Thiele, Catherine; Casey, Joanne; Simon, Susan; Dole, Shelley (Australian and International Journal of Rural Education, 2023)
Attracting high quality teachers to regional, rural, and remote locations has been an issue for school communities in Australia. Research has illustrated that innovative initiatives and experiences can change pre-service teachers’ attitudes, perspectives and perceptions about regional, rural and remote schools. What is less understood is the contribution of school leaders foregrounding a place consciousness approach to spark pre-service teacher interest in undertaking professional experience placements and possible employment in their RRR schools. This paper shares research findings that identified how Far North Queensland school leaders showcased “their place” with key stakeholders and in particular with pre-service teachers. The findings affirmed notions that school leaders understand the valuable connections between rural, regional and remote pre-service professional experiences and the potentiality for high quality teachers for the long-term. Implications are drawn in relation to how school leaders create partnerships and promote their school place intentionally.